Drug repurposing of ivermectin abrogates neutrophil extracellular traps and prevents melanoma metastasis - Zhang, Hongjun; Xu, XiaoZhu; Xu, Rui; Ye, Tao (Frontiers in Oncology, 2022)
Neutrophil extracellular traps (NETs) have recently been identified to play a crucial role in cancer metastasis. However, the treatment site of melanoma is still unclear. In this work, we screened 231 molecular compounds and found that ivermectin (IVM) is a widely used antiparasitic drug. After cathepsin B (CTSB) treatment, it can significantly inhibit the formation of extracellular traps (NETs) into neutrophils. In vivo, IVM had no effect on the growth of melanoma, and IVM significantly inhibited the transformation from melanoma to lung. The level of serum mitochondrial DNA was inhibited after IVM treatment After IVM treatment of mouse melanoma, it was observed that the embryo inhibition of tumor infiltrating bone marrow was obvious, and the number of CD8+ T cells infiltrating lung tumor increased after IVM treatment in mouse melanoma model. At the institutional level, the direct interaction between IVM and gasdermin D (GSDMD) has greatly reduced the concentration of SDMX, which is crucial for the establishment of SDMX dependent networks. In vitro, CTSB was used to treat neutrophils in bone marrow. IVM pretreatment greatly promoted the establishment of networks and greatly reduced the release of extracellular granular DNA. In conclusion, our results show that IVM can be used as a feasible method for the treatment of melanoma due to its regulatory role in neutral bodies and neural networks.